1990
DOI: 10.1111/j.1365-3083.1990.tb02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Function in IDDM Patients and Healthy Individuals

Abstract: Interleukin 1 beta (IL-1 beta) and tumour necrosis factor alpha (TNF-alpha) may be pathogenetically important in insulin-dependent diabetes mellitus (IDDM), which is associated with genes of the HLA region. Since a regulatory role of HLA region genes on monokine production may exist, we looked for an association between the monokine and prostaglandin E2 (PGE2) responses of monocytes (Mo) from 20 healthy males (18-50 years) with HLA-DR types relevant for IDDM susceptibility and resistance (DR1,2, DR1,3, DR1,4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 55 publications
4
27
0
1
Order By: Relevance
“…This suggests that these ªdiabetogenicº alleles do not exert a major influence upon cytokine production in diabetic children or in their relatives. This finding is in agreement with the study of Mùlvig et al [37] who did not find a significant association between production of IL-1b and TNF-a by monocytes and HLA DR phenotype.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that these ªdiabetogenicº alleles do not exert a major influence upon cytokine production in diabetic children or in their relatives. This finding is in agreement with the study of Mùlvig et al [37] who did not find a significant association between production of IL-1b and TNF-a by monocytes and HLA DR phenotype.…”
Section: Discussionsupporting
confidence: 83%
“…It was found that HLA-DR3, DR1, DR4, and DR7 were all associated with higher TNF-␣ synthesis (Bendtzen et al, 1988, Jacob et al, 1990, Pocoit et al, 1993. By contrast, HLA-DR2 and DR5 were found to be associated with lower TNF-␣ responses (Bendtzen et al, 1988, Jacob et al, 1990, Molvig et al, 1990, Pocoit et al, 1993. It is fair to assume that these associations are due to linkage disequilibrium between the TNF-␣ gene and the HLA-DR genes.…”
Section: Genetic Regulation Of Tnf-␣ Production Association Between Hmentioning
confidence: 83%
“…Furthermore, Schueller et al (2006) suggested the likelihood that this polymorphism does not serve as a prognostic marker for elevated sepsis risk in preterm infants. Some studies demonstrate that LTA [AA] individuals are high producers of TNF in vitro (Mølvig et al 1990, Pociot et al 1993. A previous study showed that individuals with the LTA [AA] polymorphism had a significantly reduced survival rate along with high TNF concentrations in comparison to heterozygous patients (Stuber et al 1996).…”
Section: Discussionmentioning
confidence: 99%